2020
DOI: 10.1111/febs.15186
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A6 improves anti‐migratory and anti‐invasive properties of tyrosine kinase inhibitors in EGFR overexpressing human squamous epithelial cells

Abstract: Annexin A6 (AnxA6), a member of the calcium (Ca 2+ ) and membrane binding annexins, is known to stabilize and establish the formation of multifactorial signaling complexes. At the plasma membrane, AnxA6 is a scaffold for protein kinase Cα (PKCα) and GTPase activating protein p120GAP to promote downregulation of epidermal growth factor receptor (EGFR) and Ras/mitogen activated protein kinase (MAPK) signaling. In human squamous A431 epithelial carcinoma cells, which overexpress EGFR, but lack endogenous AnxA6, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…Similar to other annexins, ANXA6 binds to negatively charged phospholipids, cholesterol, and nucleotides, as well as a large number of proteins in a Ca 2+ -dependent manner to activate cell membranes in a dynamic, reversible, and regulated manner [ 32 , 33 ]. ANXA6 has been widely studied in cancer, but based on the type and degree of malignancy of the tumor, ANXA6 can have tumor-inhibitory activity or tumor-promoting activity [ 34 ]. We performed proteome sequencing by collecting samples from the anterior section of the maximum diameter of the intrarenal aorta in patients with AAA then found that ANXA6 was highly expressed in AAA tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other annexins, ANXA6 binds to negatively charged phospholipids, cholesterol, and nucleotides, as well as a large number of proteins in a Ca 2+ -dependent manner to activate cell membranes in a dynamic, reversible, and regulated manner [ 32 , 33 ]. ANXA6 has been widely studied in cancer, but based on the type and degree of malignancy of the tumor, ANXA6 can have tumor-inhibitory activity or tumor-promoting activity [ 34 ]. We performed proteome sequencing by collecting samples from the anterior section of the maximum diameter of the intrarenal aorta in patients with AAA then found that ANXA6 was highly expressed in AAA tissue.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, AnxA6 overexpression promoted PKCα-and p120GAPmediated EGFR and Ras inactivation, respectively, inhibiting anchorage-independent growth of EGFR overexpressing and ER-negative breast cancer cell lines, A431 migration, invasion and A431 xenograft growth. Furthermore, elevated AnxA6 scaffold levels contributed to improving the efficacy of tyrosine kinase inhibitors (TKIs) targeting EGFR to reduce growth, migration, and invasive properties of EGFR overexpressing A431 carcinoma cells [240][241][242]245].…”
Section: Annexin A6mentioning
confidence: 99%
“…Tumor promotor breast cancer [246], cervical cancer [251], esophageal cancer [252], melanoma [252], ovarian cancer [253], pancreatic cancer [254][255][256], women's thyroid cancer [257] Tumor suppressor A431 epithelial carcinoma [240][241][242]245], breast cancer (TNBC, EGFR overexpressing and ER-negative) [239][240][241]246], cervical cancer [249], gastric cancer [248], HCC [250] Chemotherapy response TNBC [239,247,258], gastric cancer [259] On the other hand, tumor promoter activities of AnxA6 have also been reported, with AnxA6 displaying pro-invasive functions in invasive breast cancer cells [239,246]. In gastric cancer, AnxA6 conferred drug resistance via β1 integrin and FAK activation [259].…”
Section: Contribution Of Anxa6 To Tumorigenic Outcomes Cancer Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…In human squamous A431 epithelial carcinoma cells, which overexpress EGFR but lack endogenous AnxA6, stable expression of AnxA6 was associated with reduced cell growth [ 79 ]. The ectopic AnxA6 expression in these cells led to growth arrest in the G1 phase of the cell cycle, longer doubling times, contact inhibition upon confluence and reduced proliferation when cultured in low serum media [ 80 ]. Furthermore, stable AnxA6 expression in A431 xenografts also reduced tumor growth in vivo [ 79 ].…”
Section: The Multiple and Diverse Roles Of Anxa6 In Tumor Cell Gromentioning
confidence: 99%